Oral Vitamin D Supplementation as Add-On Therapy in Adult Patients with Atopic Dermatitis - Febrianto, Bobby; Prasetyadi Mawardi; Harijono Kariosentono (HM Publisher, 2023)
Background: Recent studies have highlighted the possible role of vitamin D in atopic dermatitis (AD) so that it can be used as therapeutical of AD. The aim of study to evaluate the effect of vitamin D supplementation as add-on therapy in adult patients with AD. Methods: Twenty-four adult patients with AD were included in a randomized, double-blind, placebo-controlled trial study. This study was conducted in Dr. Moewardi General Hospital Surakarta, Indonesia, from February to March 2023. Subjects were randomly assigned to oral cholecalciferol 5,000 IU/day versus placebo for 4 weeks and all subjects were given emollient. The severity of AD was evaluated by using scoring of atopic dermatitis (SCORAD) before and after the trial. Results: Compared to placebo, vitamin D supplementation for 1 month obtained clinically and statistically improvement in SCORAD score compare to control (-4.508 : 4.500, p= 0.000). Moreover, vitamin D supplementation had strong negative correlation to SCORAD score after the trial (r= -0.780, p= 0,000). There were no adverse effects in either group. and Conclusion: Clinical improvement was achieved after vitamin D supplementation as add-on therapy in adult patients with AD.